Some Ethical Questions in Particle Physics - Hans Peter Beck; Ivan Melo; Thomas Naumann (Communications - Scientific letters of the University of Zilina, 2017)
Authors will discuss a few ethical questions in today‘s particle physics: high costs and purported dangers of Big Science projects, relevance of fundamental research for society and the way particle physicists fill their duty to communicate with the public. Examples will be given including the story of a possible mini-black hole creation at CERN and two outreach activities for high school students, International Particle Physics Masterclasses and Cascade competition.